Zmečkana zastava - Rupel, Dimitrij (Teorija in praksa, 2016)
The article presents new historical facts and personal observations concerning Slovenia's accession to membership of the United Nations (UN) in 1991. Personal comments are connected with the author's diplomatic career and his experience at the helm of the Foreign Ministry between 1991 and 2008. The author compares the UN with other international organisations, and finds that it has hardly adapted to the circumstances that have arisen since the end of the Cold War. From this point of view, the author considers as interesting the sympathies the UN enjoys in (mostly) the left-leaning part of the Slovenian political community. The lively interest of Yugoslav diplomats from Slovenia in positions within the UN system before 1992 is also mentioned. The article details the moment when Slovenia became the 176th member of the organisation. He describes the structure and operation of the UN system, and emphasises the Slovenian foreign policy after the fall of the Berlin Wall. In connection with these, he discusses new challenges, particularly the migrant/refugee crisis and solidarity. He finds that the UN did not distinguish itself in resolution of the Yugoslav crisis. He sums up his speech at the General Assembly in New York in autumn 2006 and his conversation with Ban Ki-moon in 2008 when Slovenia held the Presidency of the EU. According to the author, the UN needs reform but, given the interests of the permanent members of the Security Council, there is little hope of seeing that happen soon.
Keywords: International organizations; International politics; Mednarodna politika; Mednarodne organizacije; Organizacija združenih narodov; Reforme; Reforms; Slovenia; Slovenija; slovenski politiki